The Argentine political and economic paradox - Juan Manuel Abal Medina; Andrea Ariza (Ибероамериканские тетради)
Unlike most Latin American nations, Argentina experienced a situation of partisan political stability in a context of consistently deteriorating macroeconomic conditions. Other countries in the region, meanwhile, have suffered profound crises and political transformations with notable stability in macroeconomic indicators. That is why the article investigates the causes of this paradox experienced by Argentina and aims to identify the causes of this institutional political stability that is maintained despite the macroeconomic disorder, the strong polarization and the deterioration of the social situation. To carry out this task, the article details the situation of the countries of the region based on the study of various economic indicators and then describes the political and economic situation in Argentina.